The association between urinary kidney injury molecule 1 and urinary cadmium in elderly during long-term, low-dose cadmium exposure: a pilot study - Dewitte Harrie; Reynders Carmen; Rigo Jean-Michel; Van Kerkhove Emmy; Nawrot Tim S; Munters Elke; De Winter Liesbeth M; Pennemans Valérie; Carleer Robert; Penders Joris; Swennen Quirine (BMC, 2011)
Abstract Background Urinary kidney injury molecule 1 is a recently discovered early biomarker for renal damage that has been proven to be correlated to urinary cadmium in rats. However, so far the association between urinary cadmium and kidney injury molecule 1 in humans after long-term, low-dose cadmium exposure has not been studied. Methods We collected urine and blood samples from 153 non-smoking men and women aged 60+, living in an area with moderate cadmium pollution from a non-ferrous metal plant for a significant period. Urinary cadmium and urinary kidney injury molecule 1 as well as other renal biomarkers (alpha1-microglobulin, beta2-microglobulin, blood urea nitrogen, urinary proteins and microalbumin) were assessed. Results Both before (r = 0.20; p = 0.01) and after (partial r = 0.32; p < 0.0001) adjustment for creatinine, age, sex, past smoking, socio-economic status and body mass index, urinary kidney injury molecule 1 correlated with urinary cadmium concentrations. No significant association was found between the other studied renal biomarkers and urinary cadmium. Conclusions We showed that urinary kidney injury molecule 1 levels are positively correlated with urinary cadmium concentration in an elderly population after long-term, low-dose exposure to cadmium, while other classical markers do not show an association. Therefore, urinary kidney injury molecule 1 might be considered as a biomarker for early-stage metal-induced kidney injury by cadmium.